Farmers’ willingness to adopt daylily forage technology in Northern Shanxi of China - Hou, Xiangjuan; Li, Qidong; Jiang, Qishen; Zheng, Minna; Li, Chunyan; Yin, Yanting; Gao, Changyu; Liu, Cunzhen; Hou, Xiangyang (Frontiers in Sustainable Food Systems, 2025)
IntroductionThe transformation of the food structure is accelerating in China, and the shortage of feed grains is the main limiting factor. Traditional feed production and feeding modes no longer meet the requirements for high-quality livestock and poultry breeding. Therefore, China’s forage industry must fully utilize its resource endowment advantages. This study explores two aspects: first, the research on the impact of personal, family, planting, and other characteristics on farmers’ willingness to adopt the forage utilization technology of stems and leaves of Hemerocallis citrina Baroni (Hc-FUT); and second, the influence of behavioral attitudes, subjective norms, and perceived behavioral control on farmers’ willingness to adopt Hc-FUT, based on the Theory of Planned Behavior (TPB).MethodsData were obtained from 225 farmers in the Yunzhou District, Datong City, Shanxi Province, China. A logistic regression model was used to examine the impact of the four characteristics on farmers’ willingness to adopt Hc-FUT, and a structural equation model was used to examine farmers’ willingness to use Hc-FUT based on TPB. SPSS 27 and AMOS 26were used for analysis.ResultsThe results show that farmers who used Hc stems and leaves to feed livestock were more willing to adopt Hc-FUT. Greater government support and increased usage of the technology positively correlated with a higher willingness among farmers to adopt it. Both subjective norms and perceived behavioral control had a significant positive impact on adoption intention, whereas subjective norms also positively impacted behavioral attitudes.